Towards precision β-decay measurements with laser cooled 35Ar. (July 2015) - Glover, R D; Lenaers, F; Velten, Ph; Finlay, P; Couratin, C; Hayen, L; Severijns, N; Bastin, T
Synopsis: We present modeling and preliminary experimental results towards the development of our magnetooptical trap (MOT) setup and polarisation scheme for 35 Ar. The atomic beam that is used for loading the MOT includes a novel transverse cooling arrangement based on a frequency broadened 'white-light molasses'. Our modeling shows that, under certain experimental conditions, such a setup can be beneficial in comparison to conventional transverse cooling techniques. We will report on experimental realization of such a setup.